2009
DOI: 10.1002/ajmg.a.32838
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of congenital heart defects in 87 consecutive patients with Brachmann‐de Lange syndrome

Abstract: Congenital heart defects (CHDs) have been estimated to occur in approximately 20% of patients with Brachmann-de Lange syndrome (BDLS, also known as Cornelia de Lange syndrome, OMIM 122470). We report on the results of a prospective echocardiographic evaluation of a cohort of 87 Italian BDLS patients with longitudinal follow-up from 5 to 12 years. A cardiac anomaly was identified in 29/87 (33.3%) including 28 (32.2%) patients with a structural CHD, and an additional patient (1.2%) with isolated non-obstructive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 21 publications
5
30
1
3
Order By: Relevance
“…Limb reduction defects were found in seven individuals with an identified mutation, all of which were in NIPBL (see online supplementary table S4). Heart defects (primarily affecting the septum) were found in 32% of individuals with an NIPBL mutation, similar to the one-third reported in a previous study 42. Two individuals with HDAC8 mutations also had septal defects, close to the 36% previously reported 12.…”
Section: Discussionsupporting
confidence: 86%
“…Limb reduction defects were found in seven individuals with an identified mutation, all of which were in NIPBL (see online supplementary table S4). Heart defects (primarily affecting the septum) were found in 32% of individuals with an NIPBL mutation, similar to the one-third reported in a previous study 42. Two individuals with HDAC8 mutations also had septal defects, close to the 36% previously reported 12.…”
Section: Discussionsupporting
confidence: 86%
“…Heart and gut abnormalities are prominent in CdLS, and among the primary causes of morbidity and mortality [16],[17],[67]. Marked L/R asymmetry in the severity of defects in CdLS (e.g., in limbs; [17]), together with the occurrence of intestinal malrotation [16], suggest that overall L/R patterning is also disturbed in this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Although the diagnosis of CdLS is made primarily based on the aforementioned features, congenital heart disease (CHD) is a commonly recognized feature of CdLS. The estimated prevalence of CHD in CdLS varies between 14% and 70% in previously studied patient cohorts of between 10 and 310 individuals, with several studies reporting a prevalence near 25% [Hawley et al, 1985; Robinson et al, 1985; Jackson et al, 1993; Kousseff et al, 1994; Mehta and Ambalavanan, 1997; Tsukahara et al, 1998; Barisic et al, 2008; Selicorni et al, 2009]. The largest group published to date by Jackson et al included 310 patients, 25% of whom had a heart condition as indicated on a parent questionnaire, with 14% having a confirmed congenital heart defect.…”
Section: Introductionmentioning
confidence: 99%
“…The largest group published to date by Jackson et al included 310 patients, 25% of whom had a heart condition as indicated on a parent questionnaire, with 14% having a confirmed congenital heart defect. A systematic evaluation of 87 patients for CHD reported by Selicorni et al [2009] revealed a prevalence of 33%. The estimated rates of CHD may vary, but nonetheless account for a significant proportion of the morbidity and mortality associated with CdLS [Beck and Fenger, 1985].…”
Section: Introductionmentioning
confidence: 99%